Comparative Study between Relational Database System (RDBMS) and Object Relational Database System (ORDBMS) in Data Modelling and Database Languages - Abdul Jalii, Farhana (Universiti Teknologi Petronas, 2006)
This paper presents comparative study between Relational Database Management System (RDBMS) and Object Relational Database Management System(ORDBMS). The objective are to develop two systems with different models; Relational Database Management System (RDBMS) and Object-Relational Database Management System (ORDBMS) and also to choose which model is better from user and designer's point of view in terms of data modeling. Several problems are being identified in order to know which model is better; Relational Database Model or Object-Relational Database. Model approach. Similarities and differences between the two models based on criteria such as data modeling are compared. This is to provide guidelines on which model users or designers to choose from based on different type of data that they wish to accommodate. The scope of research is limited to be on the development of RDBMS and ORDBMS. This project involves project planning, requirements gathering, requirements analysis, logical database design, physical database design and finally testing phase. Thus, for the data collection, a research and a survey has been conducted through readings and interviews. By developing this comparative study, this project is expected to be implemented in Admission and Registration Unit in which it can serve the better performance of database.